Effect of npk on the growth rate of ocimum basilicum - Nur Khairunnisa Ismail, - (2011)
The study of the effect of fertilizer on the growth rate of Ocimum basilicum was carried out. The experiment was conducted to find the best amount of fertilizer which is the most effective to be used in the plantation of basil in order to get the best quality of seeds. Complete Randomize Block Design (CRBD) is used as an experiment's design.The experiment was done by using four (4) different amount of treatment of green NPK 15:15:15. Each treatment had five (5) samples. The growth of each crop had been observed every week. The statistical analysis that had been observed was the height, the number of leaves and the diameter of stem. Other than that, the side information that had been taken were the colour of leaves, the vein of leaves, the odour and the seed's quality of each treatments respectively. The result of the experiment proved that the most effective amount of green NPK fertilizer was 20g per pot with two times a week applied could produce high quality of seeds, high quality of leaves with odour.